2008
DOI: 10.1530/eje-07-0515
|View full text |Cite
|
Sign up to set email alerts
|

Body mass index and ovarian function are associated with endocrine and metabolic abnormalities in women with hyperandrogenic syndrome

Abstract: Background: The aim of this study was to evaluate associations of clinical features, such as hirsutism, polycystic ovaries (PCOs), ovulatory dysfunction, and body mass index (BMI) R25 kg/m

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
51
4
8

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(68 citation statements)
references
References 34 publications
5
51
4
8
Order By: Relevance
“…In contrast, in two more recent small studies (nZ184 and nZ118 respectively) that analyzed patients with amenorrhea separately from patients with oligomenorrhea, only the former had more pronounced IR than patients with regular menses (12,13). Markers of IR did not differ between patients with oligomenorrhea and patients with regular menses (12,13). We also observed that women with regular menstrual cycles alternating with secondary amenorrhea were more insulin resistant than women with regular menstrual cycles alternating with oligomenorrhea.…”
Section: Tablecontrasting
confidence: 81%
See 3 more Smart Citations
“…In contrast, in two more recent small studies (nZ184 and nZ118 respectively) that analyzed patients with amenorrhea separately from patients with oligomenorrhea, only the former had more pronounced IR than patients with regular menses (12,13). Markers of IR did not differ between patients with oligomenorrhea and patients with regular menses (12,13). We also observed that women with regular menstrual cycles alternating with secondary amenorrhea were more insulin resistant than women with regular menstrual cycles alternating with oligomenorrhea.…”
Section: Tablecontrasting
confidence: 81%
“…However, the latter studies did not differentiate between patients with oligomenorrhea and amenorrhea (10,11). In contrast, in two more recent small studies (nZ184 and nZ118 respectively) that analyzed patients with amenorrhea separately from patients with oligomenorrhea, only the former had more pronounced IR than patients with regular menses (12,13). Markers of IR did not differ between patients with oligomenorrhea and patients with regular menses (12,13).…”
Section: Tablementioning
confidence: 77%
See 2 more Smart Citations
“…All of the assays were carried out in a routine diagnostic endocrine laboratory. TT, DHEAS, SHBG, E, PRL, LH, and FSH were measured with chemiluminescent enzyme immunoassays (Immulite 2000; Siemens Medical Solutions Diagnostics Ltd, Bad Nauheim, Germany), as previously described in detail (25)(26)(27)(28)(29)(30)(31)(32). For the TT-assay, the intraassay coefficients of variation (CV) were 16.3, 11.7, and 10.0% at the levels of 0.93, 2.98, and 5.26 nmol/l.…”
Section: Hormone Measurementsmentioning
confidence: 99%